Perbandingan Tiga Metode Kreatif dalam Meningkatkan Minat Belajar Ritme Siswa Sekolah Dasar - Putri Andani Intan Permatasari; Resa Respati; Aini Loita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the eurhythmics, orff, and rhythm syllable teaching methods on student interest in rhythm learning in elementary schools. Using a quasi-experimental design with a Post-Test Only Non-Equivalent Multiple Groups model, the study involved 38 first-grade students at SDN 133 Jalan Anyar, Bandung. Data were collected through a Likert scale questionnaire that underwent validity and reliability testing. Statistical analysis was performed using the KruskalWallis test and post hoc tests to identify significant differences between groups. The results showed that the rhythm syllable method yielded the highest average interest score (69.46), followed by the orff method (67.46), and the eurhythmics method (63.00). The Kruskal-Wallis H test indicated significant differences between the classes (p = 0.000), with the rhythm syllable and orff methods showing greater effectiveness in enhancing student interest compared to the eurhythmics method. These findings suggest that methods based on active, experiential learning, such as rhythm syllable and orff, are more effective in increasing student interest in rhythm learning. Therefore, it is recommended to integrate these methods into music education to create a more engaging and participatory learning environment.